2008
DOI: 10.1007/s00436-008-1276-x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic relationships of Habronema microstoma and Habronema muscae (Spirurida: Habronematidae) within the order Spirurida inferred using mitochondrial cytochrome c oxidase subunit 1 (cox1) gene analysis

Abstract: The present study investigated genetic variability within a population of Habronema microstoma and Habronema muscae (Spirurida: Habronematidae) affecting horses in an endemic area of central Italy using polymerase chain reaction (PCR)-coupled sequencing of the mitochondrial cytochrome c oxidase subunit 1 gene (cox1). No different cox1 sequences were detected in any of the H. muscae individual, while two haplotypes representing H. microstoma individuals differed for one substitution. The pairwise distance betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
2
5
0
Order By: Relevance
“…malayi and D . immitis (posterior probability = 1.00), consistent with results of previous studies [14,21,46]. …”
Section: Resultssupporting
confidence: 91%
“…malayi and D . immitis (posterior probability = 1.00), consistent with results of previous studies [14,21,46]. …”
Section: Resultssupporting
confidence: 91%
“…Our results support the views of the latter authors because we found differences in both morphology and gene (cox1) sequence. Here, we demonstrated an 11% difference in the mtDNA cox1 gene sequence between C. felineus and C. subaequalis, which is consistent with that found between other species of spirurids (Traversa et al, 2007;Iorio et al, 2009). Some accounts of Cylicospirura spp.…”
Section: Discussionsupporting
confidence: 90%
“…Trees before convergence were discarded to reconstruct the resulting Bayesian consensus tree with posterior probabilities. All trees were reconstructed using Strongyloides stercoralis as a putative outgroup, because it has been used in several other phylogenetic studies involving spirurids (e.g., Traversa et al, 2007;Iorio et al, 2009). Interspecific and intraspecific pairwise distances between the two Cylicospirura species sequences and those from closely related genera were calculated using MEGA4 with the Kimura-2 parameter model including all codon positions.…”
Section: Phylogenetic Analysismentioning
confidence: 99%
“…Although there has recently been a relatively wide application of phylogeography, it is mainly employed for studies on vertebrates with limited usage on invertebrates, especially on parasites (Nieberding et al 2005;Iorio et al 2009). In these studies, mitochondrial DNA fragments were the most frequently used molecular markers (Nieberding et al 2004;Picard et al 2007) because mitochondrial genes were recognized as maternal inheritance, there's no occurrence of reorganization between genes, they are able to reflect the maternal evolutionary history , and are particularly applicable to identify similar species and subspecies (Blouin et al 1997).…”
Section: Introductionmentioning
confidence: 99%